Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. II. The vascular flora - Rhett D. Harrison; Roy Banka; Ian W. B. Thornton; Mike Shanahan; Ruby Yamuna (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. II. The vascular flora - Rhett D. Harrison; Roy Banka; Ian W. B. Thornton; Mike Shanahan; Ruby Yamuna (Journal of Biogeography, 2001)
Aim Long Island erupted catastrophically in c . 1645 with the probable destruction of its entire biota. While several expeditions have visited the island since, no survey of its flora has been published. In 1968 a small island, Motmot, emerged from its caldera lake. Motmot has been surveyed several times but not since 1988. The aim of this study was to investigate the colonization by vascular plants of this interesting nested pair of islands. Location Long Island is 55 km off the northeast coast of Papua New Guinea (PNG) and Motmot lies in its fresh water caldera lake, Lake Wisdom, c . 4 km from the rim of the surrounding volcano. Methods We conducted a complete survey of the vascular plants on Motmot and made ad hoc collections on Long Island, including surveying three small plots, over 15 days in 1999. In addition, we incorporated data from several collections lodged at the regional herbarium in Lae. Data on seed dispersal syndromes and plant habit were obtained from the literature. Results We recorded 305 species of vascular plants from Long Island, but most trees were small and the species diversity was low. Motmot was still very sparsely vegetated and only forty‐five species of vascular plants were found. Communities on Motmot were unspecialized and common species widespread. The flora of Motmot was not significantly different from that on Long Island in terms of the number of species amongst higher taxa, seed dispersal syndromes or plant habits. Main conclusions Low rainfall combined with very porous soils may be responsible for the small stature and low diversity of the forest on Long Island's caldera rim. The absence of specialist littoral species on Motmot, as a result of its landlocked situation, is probably responsible for the very slow species recruitment on the island. This community appears to be functionally important for colonization by comparison with other small volcanic islands in a marine situation.